Does journaling practice affect EFL students’ writing ability? - Rusmiati, Rusmiati; Maharami, Kin; Shaumiwaty, Shaumiwaty (Department of Applied Linguistics, FBSB, Universitas Negeri Yogyakarta, 2025)
Finding ideas to write about is a common challenge for many EFL learners in developing their writing skills. This study aimed to investigate whether writing about daily activities (i.e., journaling) improves the writing ability of EFL students at a junior high school in Aceh Tengah. A quantitative, experimental research design was employed. The sample consisted of 46 eighth-grade students, with 22 in the experimental group and 24 in the control group. Pre- and post-tests were used to measure the students’ performance before and after the intervention. Results showed that the experimental group’s mean score increased significantly from 48 (pre-test) to 82 (post-test). A t-test analysis revealed that t(44) = 4.92, p < .05, indicating a significant difference between the groups. This result suggests that journaling practice had a statistically significant positive effect on the EFL students’ writing ability.